Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Menulis Teks Laporan Hasil Observasi - Cindy Arveni; Abdul Azis; Yuli Astuti Ameliah (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2024)
This study aims to describe the effect of using the Problem Based Learning model on the learning outcomes of writing observation report texts of class X students of SMK Negeri 10 Makassar. This research is a type of experimental research. The research design used was One Group Pretest-Postest Design. Data analysis techniques used in this research are descriptive statistics and inferential statistics. The results showed that the learning outcomes of writing observation report text before using the Problem Based Learning model were categorized as less capable with an average score of 66.94. The learning outcomes of writing observation report text after using the Problem Based Learning model were categorized as proficient with an average score of 84.33. There is an effect of Problem Based Learning model on the learning outcomes of writing observation report text of Class X students of SMK Negeri 10 Makassar.